Investigation of bioclimatic design features in vernacular architecture of Northeast India: Case studies of Assam-type houses and stilt houses (Chang Ghar) in Assam, India - Choudhury, Ankita Sen Deka; Chettry, Vishal (National Institute of Science Communication and Policy Research, 2023)
Bioclimatic design features in the buildings are based on surrounding geography and climate to create comfortable and healthy spaces. These features are observed in the vernacular architecture styles across the regions of India. Various bioclimatic design strategies are also observed in Northeast India; however, they are less focused when compared to other regions of India. Therefore, this paper attempts to investigate bioclimatic features in the vernacular architecture of Northeast India, wherein it focuses on two typologies, i.e., Assam-type house and Stilt houses (Chang Ghar). A qualitative analysis based on the site surveys was done to identify bioclimatic features used in the two selected typologies. The parameters selected to investigate bioclimatic features include the type of construction materials and methods used; the spatial arrangement of spaces; orientation and layout of the building; wall thickness; nearby open spaces; vegetation and water bodies; openings and ventilation; window to wall ratio; plinth height; design and material of shading devices; structure, height, and material of ceiling, any other special features. Overall, the results indicated that Assam-type houses and stilt houses are highly responsive to the local climate, utilizes locally available materials (bamboo, wood, and mud), and reflects the living style, customs, and socio-economic conditions. The outcome of this qualitative study was the identification of multiple bioclimatic features observed in both typologies. The recommendations from this study can act as a reference for designing buildings that shall promote sustainable built environments as per United Nations Sustainable Development Goal number 11 (Sustainable cities and communities).
This paper published with affiliation IIT (BHU), Varanasi in open access mode.
Keywords: Assam-type house; Bioclimatic design; Northeast India; Stilt house; Vernacular architecture